2010
DOI: 10.1097/mrr.0b013e328332f617
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intensive versus nonintensive physiotherapy in children with cerebral palsy: a meta-analysis

Abstract: studies that included therapies not generally used in 'so-called' conventional treatment (i.e. constraint, taping). Treatment effects were combined using the weighted mean difference method. Fixed and random effect meta-analyses were carried out and results were compared. Heterogeneity was also assessed. Funnel plots were examined and the presence of small-study effects was tested. Intensive therapy tended to have a greater effect than nonintensive therapy (1.32; 95% confidence interval: 0.55-2.10). The effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 17 publications
0
36
0
2
Order By: Relevance
“…Previous studies have shown that intensive PT can have an effect in developmentally delayed children, including CP patients (5678913141516). Our results showed a significant change in GMFM-88 score, of 4.67 ± 3.93, after 8 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that intensive PT can have an effect in developmentally delayed children, including CP patients (5678913141516). Our results showed a significant change in GMFM-88 score, of 4.67 ± 3.93, after 8 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, intensive therapy tended to have greater effects on functional motor outcomes (with modest effect sizes) than non‑intensive therapy (5). There is no precise consensus regarding the intensity and duration of intensive therapy, or concerning ‘intensive rehabilitation.’ In addition, the form that intensive rehabilitation treatment takes may vary according to regional facilities, manpower and medical care systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the current approach is very early detection and referral of a condition which can respond to rehabilitation in early childhood. [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…Systematic study reviews on the effectiveness of physical therapy interventions in children with CP show limited evidence of effectiveness with few randomized controlled clinical trials [6]. Nevertheless, it has been demonstrated that high-intensity and task-specific programs have resulted in improved strength and functional performance that were sustained over time [7], [8].…”
Section: Introductionmentioning
confidence: 99%